An educational intervention for nurses in the upper east region of Ghana on patient and family centered care implementation in the peri-operative context - Adugbire, Atinyagrika Bernard (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.